IMPLEMENTASI KECERDASAN MAJEMUK (MULTIPLE INTELLIGENCE) DI SEKOLAH DASAR - Ari Susandi; Marwan Marwan (Universitas Ahmad Dahlan, 2020)
AbstractMultiple intelligence is indeed something that is owned by every individual from the level of basic education, the type of intelligence that exists in each individual is indeed very determining their success and success in achieving a goal from which they aspire. what we can see at this time is that the process of learning activities at the elementary school level still shows that the principle of multiple intelligence itself is indeed integrated with one another teaching materials which will always have the capacity to interact with students and also educators, the development of participants students at the elementary school level always continue to develop rapidly which in this case includes spiritual intelligence, social intelligence, intellectual intelligence and individuality intelligence in students who have the principle that the learning process remains in the context of science based on Pancasila principles and religious teachings.